Methods for Euclidean geometry - Byer, Owen D.; Lazebnik, Felix; Smeltzer, Deirdre Longacher (Dover books on mathematics, 2021)
"This book explores the application of a broad range of mathematical techniques to the solution of Euclidean problems"--